Mot bättre service – utveckling av Folkpensionsanstaltens e-tjänster - Turunen, Marjukka (Klart språk i Norden, 2014)
In Finnish Social Insurance Institution (Kela) all the operational IT-systems and network services will be renewed during the next ten years. The renewal project is part of Kela´s strategy. What customers need, is the key to all the renewal projects because customers play an important role in developing the services. In the Arkki project the focus is mainly on network services. Kela is investing in its network service channel because these services have been increasingly popular amongst customers. Through the internet services customers can e.g., check their personal data on benefits, apply for benefits and calculate the amounts of benefits. Students, families and unemployed are the biggest customer groups that use Kela´s internet services. Customers have given Kela positive feedback for the internet services.